Cognitive Impairment and Endoplasmic Reticulum Stress Induced by Repeated Short-Term Sevoflurane Exposure in Early Life of Rats - Shen, Fu-Yi; Song, Ying-Cai; Guo, Fei; Xu, Zhen-Dong; Li, Qian; Zhang, Bing; Ma, Yu-Qin; Zhang, Yue-Qi; Lin, Rong; Li, Yang; Liu, Zhi-Qiang (Frontiers in Psychiatry, 2018)
Sevoflurane is one of the most commonly used volatile anaesthetic for children, but the safety of prelonged or repeated sevoflurane exposure to infants or children is challenged in clinic. Here we investigated the effects and time scope of sevoflurane on rats in early life. Our behavioral results indicate that repeated short-term sevoflurane exposure to new born rat caused learning and memory impairment, while a single exposure of sevoflurane to rats is relatively safe. Further mechanism investigation revealed that repeated sevoflurane exposure impaired long-term potentiation (LTP), down-regulated the expression of certain synaptogenesis-related proteins (GluR1, PSD95) and up-regulated ER stress related proteins in the hippocampus. The endoplasmic reticulum (ER) stress inhibitor, Tauroursodeoxycholic acid (TUDCA), could reverse the changes in synaptic plasticity protein levels. Our results provide new evidences for the clinic concerns of repeated anaesthetic exposure of sevoflurane.